Investigating the Present Condition of the Textile Industry in Bangladesh on Sustainability Practices - Md Tahzibul Haque; Ismail Maakip; M. K. Wan Ibrahim; Khalilullah Muhammad Bayezid; Md. Nura Alam Shiddique; Md. Mostafizur Rahman; Selim Reza; Sumaiya Siddika (The International Journal of Science, Mathematics and Technology Learning (IJSMTL), 2024)
With the primary objective of gaining insights into the industry's prevailing conditions and potential avenues for growth, the study employed interviews as the primary data collection method. The research conducted in-depth interviews with key stakeholders, including industry experts, policymakers, manufacturers, and workers, to capture multifaceted perspectives and ensure a comprehensive understanding of the sector. The research unraveled the inherent strengths that bolster the Bangladesh textile industry's position in the global market through rigorous thematic data analysis and interpretation. Additionally, the study identified critical weaknesses that require targeted interventions to enhance competitiveness and sustainability. Moreover, the research unearthed potential opportunities for further growth and expansion in an ever-evolving global economic landscape. Finally, the analysis revealed looming threats that could pose challenges to the sector's progress in the future.